Chikungunya fever in Africa: a systematic review. (2nd April 2020) - Russo, Gianluca; Subissi, Lorenzo; Rezza, Giovanni
ABSTRACT: Since the identification of chikungunya virus (CHIKV), sporadic cases and outbreaks were reported in several African countries, on the Indian subcontinent, and in south-east Asia. In the last 20 years, there is a growing number of reports of CHIKV infections from African countries, but the overall picture of its circulation at the continent level remains ill-characterized because of under-diagnosis and under-reporting. Moreover, the public health impact of the infection in Africa is generally poorly understood, especially during outbreak situations. Our work has the aim to review available data on CHIKV circulation in Africa to facilitate the understanding of underlying reasons of its increased detection in the African continent.